2021
DOI: 10.1021/acs.jpcc.0c08324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Halogen Ions on the Low Thermal Conductivity of Cesium Halide Perovskite

Abstract: The lattice dynamics of CsSnX 3 (X = Cl, Br, and I) and CsPbI 3 , which are low-thermal-conductivity materials, are investigated using first-principles phonon calculations. Because of the strong lattice anharmonicity and the accompanying instability of high-temperature cubic phases, the self-consistent phonon theory, which can incorporate the effect of lattice anharmonicity at a mean-field level, is applied in this study. The calculated lattice thermal conductivity reproduced a low thermal conductivity, as sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
(66 reference statements)
0
22
0
Order By: Relevance
“…12 It was reported that the k L of CsSnCl 3 is lower than that of CsSnBr 3 , which originates from the short phonon lifetimes in CsSnCl 3 . 13 The k L of CaO was also found to be lower than that of CaS, whereas the k L of CaO exceeds that of CaS under a compressive strain of over 2%. 14 In this work, the anharmonic lattice dynamics of CsX is investigated to elucidate the pressure dependence of k L of CsX, as well as the unexpected higher k L of CsI.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…12 It was reported that the k L of CsSnCl 3 is lower than that of CsSnBr 3 , which originates from the short phonon lifetimes in CsSnCl 3 . 13 The k L of CaO was also found to be lower than that of CaS, whereas the k L of CaO exceeds that of CaS under a compressive strain of over 2%. 14 In this work, the anharmonic lattice dynamics of CsX is investigated to elucidate the pressure dependence of k L of CsX, as well as the unexpected higher k L of CsI.…”
Section: Introductionmentioning
confidence: 88%
“…The third-order force constants were extracted based on the compressive sensing approach using the least absolute shrinkage and selection operator (LASSO) technique, 15,17 which was often used for strongly anharmonic materials. 13,18,19 The third-order force constants were extracted from the following LASSO equation:…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported, lead-based halide perovskites possess ultra-low thermal conductivities (0.37, 0.51, and 0.73 W m −1 K −1 for MAPbI 3 , 12 MAPbBr 3 , 13 and MAPbCl 3 , 14 respectively) that are closely related to the atomic structure, 15 atomic disorder, crystal anharmonic vibration, crystal structure, and electron pair. 16 The control in thermal conductivity can also be achieved by tuning the proportion of halogens 17 in tin-based perovskites 18 such as CsSnBr 3−X I X , which possesses an ultralow thermal conductivity of 0.32 W m −1 K −1 due to strong phonon scattering. Meanwhile, two-dimensional Ruddlesden− Popper perovskites such as BA 2 MA n−1 Pb n I3 n+1 (n = 1−7) have been demonstrated to alter n to exhibit lower thermal conductivity than MAPbI 3.…”
Section: Introductionmentioning
confidence: 99%
“…The first-order self-consistent phonon (SC1) theory is one of the most successful methods, which determines the renormalized phonon frequencies by the variational principle applied to the first-order cumulant expansion of the Helmholtz free energy [16,17]. Since the SC1 theory can, to a large extent, remedy the negative frequency problems of the harmonic approximation, it has been actively employed in first-principles calculations of phononrelated physics of anharmonic materials, including thermal transport [13,[18][19][20][21], phonon-limited mobility [22], bandgap renormalization [23,24], thermal expansion [25,26], and conventional superconductivity [7,12,27]. While these studies clearly demonstrate the advantage of the SC1 theory over the quasiharmonic theory and purely perturbative approaches, the quantitative accuracy of SC1 is still inadequate for strongly anharmonic materials.…”
mentioning
confidence: 99%